Aerosol characteristics in the upper troposphere and lower stratosphere region during successive and contrasting Indian summer monsoon season. (January 2018) - Srivastava, A.K.; Kumar, D.; Misra, A.; Kanawade, V.P.; Pathak, V.; Tiwari, S.; Devara, P.C.S.
Abstract: Cloud Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO)-derived aerosol vertical profiles were studied in the upper troposphere and lower stratosphere (UTLS) over the Indian summer monsoon (ISM) region during two successive and contrasting monsoon years (2008–2009). An enhanced aerosol layer was observed in the UTLS between 15 and 19 km altitude, in the vicinity of tropopause during both years. However, the optical characteristics of aerosol layers were found to be dissimilar during the two contrasting consecutive summer monsoon seasons. While the depolarization ratio of enhanced aerosol layer (exceeding 0.2) during both years suggested anisotropic nature of particles, the aerosol backscatter coefficient was observed to be more intensified with a sharp peak during the active monsoon year (2008) whereas it was relatively broader with lower magnitude during a drought year (2009). The enhanced backscatter coefficient in the UTLS was found to be closely associated with the variability in tropopause height and convection during both years, which is more pronounced during the active monsoon year as compared to a drought year. Deep convection over the ISM region may inject boundary layer aerosols into the upper troposphere as evidenced from the analysis of the outgoing long-wave radiation (OLR). Our results also showed an enhanced integrated backscatter coefficient (IBC) of about 30%, which is associated with a decrease in OLR of about 7% during the active monsoon year as compared to drought year. These findings were further corroborated using NCEP-NCAR vertical velocity and HYSPLIT air-mass backward trajectory analyses. Highlights: Aerosol profiles were investigated in the UTLS during two contrasting monsoons. Enhanced aerosol layer was identified during the summer-monsoon period. Aerosol layer was associated with tropopause height and deep convection. Results are more pronounced in active monsoon year as compared to drought year.